Analisis Kesulitan Belajar IPS dan Upaya Penanganan pada Siswa Kelas V Sekolah Dasar - Suci, Norma Atika; Istiyati, Siti; Kamsiyati, Siti (Jurnal Pendidikan Dasar, 2022)
This study aims to describe the social studies learning difficulties and the handling efforts of the fifth grade students of SD Negeri Mangkubumen Kidul. The method in this research is descriptive qualitative research. The approach in this research is a case study. The subjects of this study were 28 students V and it was found that there were 11 students with scores below the KKM. Data collection techniques used in this research are document study analysis, observation, interviews, questionnaires, and documentation. The data analysis technique uses the Miles-Huberman interactive analysis model. Activities in data analysis include collecting data, reducing data, presenting data, and drawing conclusions. The validity of the data in this study uses triangulation of sources and techniques. The results showed that 11 students scored below the KKM (Minimum Completeness Criteria) on the theme 6, 7, and 8 theme test questions. Material difficulties related to the influence of human interaction and the role of society with the natural environment, names of heroes, arrival and resistance against western nations, British colonials, Dutch colonials, economic activities, and forms of business. Based on the data analysis of the factors that cause students to have difficulty learning Social Sciences because they are not interested, a lot of material, a lot of memorization, difficult questions, easy to forget, limited learning resources in schools, limited use of learning media, lack of parental assistance. The efforts made by the teacher are to give special attention and re-explanation of the material to students who do not understand the material. Efforts made by parents are to remind children to study, provide facilities in the form of the internet, and bring in tutors or include children in tutoring. Efforts made by students are asking teachers, parents, siblings, and tutors for material, looking for material in books and the internet.